2019
DOI: 10.2139/ssrn.3320145
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Guillain-Barré Syndrome (GBS) in Latin America and the Caribbean Before and During the 2015-2016 Zika Virus Epidemic: A Systematic Review and Meta-Analysis

Abstract: BackgroundA severe neurological disorder, Guillain-Barré syndrome (GBS) is the leading cause of acute flaccid paralysis. Enhanced surveillance of GBS in Latin America and the Caribbean (LAC) following the 2015-2016 Zika virus (ZIKV) epidemic presents an opportunity to estimate, for the first time, the regional incidence of GBS. Methods and findingsFor this systematic review and meta-analysis, we searched nine scientific databases and grey literature from January 1, 1980 to October 1, 2018. Sources with primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Despite searching six databases, we found few case reports. As it was the case with Zika virus 8 , 17 , more cases may appear later in the pandemic. As the COVID-19 pandemic progresses, clinicians should be aware that GBS and other variants are possible and relevant complications.…”
Section: Discussionmentioning
confidence: 94%
“…Despite searching six databases, we found few case reports. As it was the case with Zika virus 8 , 17 , more cases may appear later in the pandemic. As the COVID-19 pandemic progresses, clinicians should be aware that GBS and other variants are possible and relevant complications.…”
Section: Discussionmentioning
confidence: 94%
“…During the 6-month period of the French Polynesia arboviral epidemic (2013-2014), 28,000 cases of ZIKV infection were observed (10% of the total population): among them, 42 cases of GBS were reported (with a pattern more suggestive of AMAN/AMSAN), versus < 2 annual usual cases in this area [55]. In Latin America and the Caribbean, GBS incidence was estimated to have increased 2.6 times during the ZIKV outbreak [56]. It was hypothesized that ZIKV-GBS may be due to dysregulation of the activity of the RNA editing enzymes [57].…”
Section: Guillain-barré Syndrome and Emerging Infectious Diseasesmentioning
confidence: 98%
“…ZIKV infection was sporadically observed in some African and Asian countries until its epidemic capacity was revealed in the southwestern Pacific Ocean (2007), South Pacific (2013-2014), then South America, Latin America and the Caribbean (2015-2016) (Fig. 3) [56]. Before 2013 ZIKV was not known to provoke neurological complications, but many cases of GBS were then linked to ZIKV, with three strains of ZIKV (two from Africa, then one from Asia that spread in the South Pacific and America) supporting an expansion of its lineage with several recombination events [55].…”
Section: Guillain-barré Syndrome and Emerging Infectious Diseasesmentioning
confidence: 99%
“…Following ZIKV infection, neurological abnormalities were reported in mouse models ( Figueiredo et al, 2019 ) as well as in clinical conditions ( Capasso et al, 2019 ; Moura da Silva et al, 2016 ). In our initial studies, we observed seizure in ZIKV infected mice while handling it, but not in CST treated ones.…”
Section: Discussionmentioning
confidence: 99%